Selected International Best Practices in Police Performance Measurement - Davis, Robert C. (RAND Corporation, 2012)
Historically, police agencies have measured their performance against a restricted set of crime-focused indicators, but modern police officers must be prepared to take on a wide variety of roles. Performance measures should be multidimensional to capture this complexity. This report describes some key considerations in designing measures to evaluate law enforcement agencies and includes a detailed review of some international best practices.